The association of sarcopenia and osteoporosis and their role in falls and fractures (literature review) - V.V. Povoroznyuk; N.V. Dedukh; M.A. Bystrytska; N.I. Dzerovych; V.S. Shapovalov (Medičnì Perspektivi, 2021)
The progressive and generalized loss of skeletal muscle mass and strength leads to sarcopenia in elderly people. A new geriatric syndrome has been revealed – osteosarcopenia (osteosarcoporosis), which combines low bone mineral density with reduced muscle mass, strength and functional activity. The review presents data on the peculiarities of manifestation of these syndromes, the mechanisms of which are multifactorial and continue to be investigated. They are associated with genetic factors, lifestyle – lack of physical activity and malnutrition. The pathogenesis of sarcopenia involves mechanisms of chronic inflammation, changes in endocrine function, disturbance of neuromuscular connections and low reparation level. Sarcopenia correlates with low quality of life, disability, and death. The review analyzes the prevalence of sarcopenia which increases with age. However, there are conflicting results in the populations, which may be related to different clinical conditions, patient area, lifestyle and the use of different assessment criteria. The analysis of sarcopenia prevalence in men and women showed ambiguous results related to the studied population, involvement of different age groups of patients, different evaluation methods. Metabolic disorders in muscular and bone tissues were summarized on the basis of the analysis of the cross-influence of regulatory factors and metabolism products of these tissues; a close metabolic and functional association between them was shown. Fat infiltration of atrophied muscles and bone marrow is common in patients with sarcopenia and osteosarcoporosis, which affects muscle and bone tissue. Lipotoxicity and local inflammation stimulate the biosynthesis of pro-inflammatory cytokines. Literature analysis has shown controversial data on the association of sarcopenia and osteosarcopenia with falls and fractures, but based on meta-analysis data, which include an extensive body of information, it should be noted that individuals with sarcopenia and osteosarcopenia are more at risk of falls and fractures and require special special attention. The most common fracture in osteosarcopenia is the hip fracture.